Study of overweight and obesity and its risk factors among adults in an adopted urban slum area of Government Medical College, Miraj - Sharma, Sachin K.; Sangrulkar, Tejaswini V.; Brahmankar, Tanuja R.; G.R., Vishwanath (International Journal Of Community Medicine And Public Health, 2017)
Background: Obesity and overweight are creating a global epidemic. In 2008, more than 1.4 billion adults were overweight worldwide. Rapidly changing diets & lifestyles are fueling the global epidemic. Once being considered as a problem related to affluence, obesity is now growing fast in many developing countries. The burden of slum population & magnitude of their health problems are on the rise. Thus, the present study was planned to determine the prevalence of overweight & obesity and its risk factors in the urban slum area. Methods: A cross sectional study was carried out among adults aged 20 – 60 years. Persons willing to participate and who were residing more than 6 months in the study area were included. The sample of 320 was calculated with absolute error of 5%. Duration of study was from Feb 2014 to Dec 2014. Pretested Predesigned Proforma was constructed and Systematic random sampling method was used for data collection. Results: In this study, the prevalence of overweight and obesity was 9.7% and 16.6% respectively. The study shows significant association between age, gender, occupation, family history of obesity, intake of calories and physical activity with overweight/obesity. Conclusions: The prevalence of obesity was more in females. Obesity can occur at any age and generally increases with age. The prevalence was more in adults who had family history of obesity. Low levels of physical activity are associated with higher prevalence. Thus, participation in household activities and regular physical exercise could help in lowering the prevalence.